The Influence of Green Human Resource Management on Sustainable Organizational Performance in IKAPI Member Companies - Dasmadi; Telly Pauline Ulviana Siwi (Fundamental and Applied Management Journal, 2026)
This study aims to analyze the influence of Green Human Resource Management (GHRM) on Sustainable Organizational Performance in IKAPI member companies in Indonesia. The research employed a quantitative explanatory approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 to examine the relationship between green HRM practices and organizational sustainability performance. Data were collected through questionnaires distributed to employees of IKAPI member companies selected using purposive sampling techniques. The findings revealed that Green Human Resource Management significantly and positively influences sustainable organizational performance through green recruitment, green training, green employee involvement, and environmentally oriented organizational policies. The implementation of GHRM practices contributes to improving environmental awareness, operational efficiency, employee engagement, organizational reputation, and long-term sustainability performance. The study also found that digital transformation and employee participation strengthen the effectiveness of sustainability-oriented organizational practices within publishing companies. However, several challenges remain, including limited organizational resources, inconsistent employee awareness, and the absence of structured sustainability evaluation systems. This research contributes theoretically by expanding the literature on GHRM within the publishing industry context and practically by providing recommendations for organizations to strengthen sustainability-oriented human resource management strategies. Therefore, GHRM can become an important strategic approach for improving sustainable organizational competitiveness in the publishing sector.